Corporate Social Responsibility (CSR) and Stakeholders Engagement: The Role of Community Participation in Nigeria - Annmarie Nkemejina Okoli; Victoria Omenebele Kaizar; Nelson Iguemedere Ofomaja; Oghenovo Maureen Atie; Samuel Ejiro Uwhejevwe Togbolo (Transpublika Publisher, 2025)
CSR is becoming a strategic approach in fostering long-term commitment with stakeholders, building trust, and addressing pressing socio-economic and environmental challenges. This study employs a quantitative research approach to examine CSR and stakeholder engagement among Nigerian firms listed on the NGX. The research focuses on 40 community leaders and 5 non-financial firms, drawing 42 respondents, which makes the population and sample size 82 respondents, which implies a purposive sampling technique. The population and sample size ensured a complete and statistically motivated analysis of CSR implementation and community participation. The study utilises the quantitative techniques, this technique allows the study to provide empirical insights into how firms participate with local communities in CSR decision-making and the overall efficiency of the participating strategies. The study findings revealed that there is low confidence in CSR, as the firms' openness about CSR strategies is still questionable to a large extent. Also, the study result indicates that community-specific resource allocation, firms' corporate transparency, and trust-building efforts must be strengthened to ensure that communities can play a meaningful role in CSR initiatives. The study concluded that CSR initiatives are widely implemented, but community involvement in decision-making as regard CSR remains inconsistent, with many firms adopting top-down approaches which tend to limit community CSR-specific needs and thereby create a lack of genuineness for stakeholder influence. It was recommended that community participation in CSR; therefore, firms should ensure communities are involved in their CSR initiatives, thereby showing transparency through proper communication.